JUVENILE OFFENDER’S PROFILE - Stołpiec, Katarzyna; Bernasiewicz, Maciej (No Limits, 2022)
Crime is a phenomenon that cannot be completely eradicated. Society’s traditions and culture, as well as the level of its economic development, are very important in maintaining the optimal happiness levels of its people. In spite of the efforts of educators and parents, who are sometimes overly preoccupied with ensuring a prosperous life for their children, they are unable to protect them from the danger of going down the road of crime.